Hidrólise enzimática do bagaço da cana-de-açúcar para posterior obtenção de álcool de segunda geração - Faria, Sâmela Paranaguá Viegas Vasconcelos (2015)
Cellulosic ethanol, also called secondgeneration ethanol, has been considered an alternative to reduce environmental and energy problems in the world because of the shortage and high prices of fossil fuels and pollution caused by them, making it necessary to invest in developing renewable energytechnologies.In this innovation context, a new use opportunity of lignocellulosic biomass is conjectured, especially in the sugarcaneindustry for second generation ethanol production. Under this scenario, the objective was to study the enzymatic hydrolysis of bagasse from sugarcane to obtain fermentable sugars for subsequent obtaining of second generation ethanol. However, it is necessary to make a pretreatment to reduce the recalcitrance of biomass in naturaand make the cellulose more accessible to enzymatic attack.In this workthe treatmentwas carried out with acid and base solution and alkaline hydrogen peroxide. Besides treatment were also studied the process variables such as enzyme concentration of 10, 15 and 20 FPU/g, the hydrolysis timeof6, 24 and 48 hours anda temperature of 40, 45 and 50°C according to an experimental design type 3³ for sugarcane bagasse samples in naturaand pretreated with two different methodologies.After statistical analysis it found that pretreatment of bagasse with acid and base was instrumental in the release of fibers and lignin removal, with response in total reducing sugar (ART) far superior tothat presented in the hydrolysis for bagasse in naturaand for bagasse pretreated with peroxide. Stillit was possible to obtain values that maximize the production of ART to bagasse pretreated with acid and base, which were enzyme concentration of 20 FPU/g, 48hours and 50°C.